Junkyard joe volume 1 ebook - Johns, Geoff (Junkyard Joe, 2023)
Throughout history, unlikely and strange heroes have risen and fallen, their identities and lives a secret. But for a Great Evil to be stopped, their stories must be told. They are The Unnamed fighting The Unknown War. From the explosive pages of GEIGER comes JUNKYARD JOE! The world knows him from the comic strip by recently retired cartoonist Muddy Davis, but the truth stretches back to the Vietnam War. The tragedies of combat and visions of a strange robot soldier that saved Muddy’s life there still haunt him. But dreams become reality when Joe mysteriously shows up on Muddy’s doorstep, warning of a new impending war.